2021
DOI: 10.1108/yc-09-2020-1213
|View full text |Cite
|
Sign up to set email alerts
|

The power of materialism among young adults: exploring the effects of values on impulsiveness and responsible financial behavior

Abstract: Purpose The purpose of this paper is to investigate the effects of values of materialism on cognitive and affective impulsiveness and responsible financial behavior among young adults. Design/methodology/approach A large-scale study (n = 483) was conducted on a sample of young adults 18 to 25 years of age in Croatia. Findings The research found that materialism has no direct effect on responsible financial behaviour (RFB), however, cognitive impulsiveness fully mediates the relationship of all three there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Based on table 6, the correlation value of materialism to financial management behaviour is very low, namely 0.19. The results of this study are in accordance with research conducted by Lučić et al (2021), who suggest no correlation between materialism and financial behaviour. Materialism does not prevent students from having good financial management behaviour.…”
Section: Mediation Testsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on table 6, the correlation value of materialism to financial management behaviour is very low, namely 0.19. The results of this study are in accordance with research conducted by Lučić et al (2021), who suggest no correlation between materialism and financial behaviour. Materialism does not prevent students from having good financial management behaviour.…”
Section: Mediation Testsupporting
confidence: 92%
“…Arofah et al (2018) suggested that materialism has a positive influence on financial behaviour. Meanwhile, Lučić et al (2021) suggested no correlation between materialism and financial behaviour. The inconsistency of these results becomes a gap to be examined further in the relationship between financial knowledge, financial attitude, locus of control, and materialism with financial management behaviour.…”
Section: Introductionmentioning
confidence: 99%
“… Lee and Chen (2021) stress that instant reactivity and convenience trigger impulsive purchase in mobile commerce. Studies have identified products that are bought impulsively, including groceries ( Inman et al, 2009 ; Bellini et al, 2017 ), financial products ( Lučić et al, 2021 ), milk tea ( Guo et al, 2017 ; Wu et al, 2021 ), necessities during COVID-19 pandemic ( Islam et al, 2021 ), “unhealthy” foods ( Verplanken et al, 2005 ), and brand-related user-generated content products ( Kim and Johnson, 2016 ). Some studies are keen to discover how different purchase channels influence impulsive buying, for instance, online markets ( Kim and Johnson, 2016 ; Guo et al, 2017 ; Aragoncillo and Orus, 2018 ; Pal, 2021 ; Rejikumar and Asokan-Ajitha, 2021 ; Wu et al, 2021 ), mobile commerce ( San-Martin and López-Catalán, 2013 ; Chen et al, 2021 ), and offline/in-store shopping ( Rook and Fisher, 1995 ; Inman et al, 2009 ; Tendai and Crispen, 2009 ; Sharma et al, 2010 ; Aragoncillo and Orus, 2018 ).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“… Rook (1987) describes impulse buying as spontaneous and hedonic purchase driven by an urgent, forceful, and persistent craving, regardless of possible consequences. Lučić et al (2021) assert that impulsive purchase is actuated by irrational emotions. Researchers also claim that impulsive purchase is the result of an irresistible reaction that is triggered by often deliberately designed stimuli ( Stern, 1962 ; Rook, 1987 ; Liu et al, 2013 ; Kim and Johnson, 2016 ; Aragoncillo and Orus, 2018 ).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…An important issue to take in consideration is that studies of materialism tend to focus on adult populations, nevertheless, the study of materialism on younger populations is relatively scarce. For example, several studies have focused on the study of materialism of higher education students and young adults (Adib & El-Bassiouny, 2012;Chaplin & John, 2010;Durvasula, & Lysonski, 2010;Goldberg et al, 2003;Karabati & Cemalcilarb, 2010;Lučić et al, 2021), however similar studies can barely be found on younger populations. Therefore, the present work explores materialism on adolescents.…”
Section: Materialism and Satisfaction With Lifementioning
confidence: 99%